FEAR OF MISSING OUT (FOMO) AND DIGITAL CREDIT: IMPLICATIONS FOR THE ECONOMIC SUSTAINABILITY OF COMMUNITIES IN DELI SERDANG REGENCY - Halomoan Siregar, August; Sardina Purba, Yessica; Hidayat, Ferry (Penerbit Lafadz Jaya, 2025)
The rapid expansion of digital technology has transformed consumption patterns, particularly in the financial sector through digital credit or Buy Now Pay Later (BNPL). While digital credit improves financial inclusion, it also heightens risks of over-indebtedness, especially when influenced by Fear of Missing Out (FOMO). This study examines the impact of FOMO on digital credit usage and its implications for household economic sustainability in Deli Serdang Regency. A quantitative survey was conducted with 400 purposively selected respondents, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results demonstrate that FOMO significantly increases digital credit usage, while both FOMO and digital credit exert negative effects on economic sustainability. The model explains 42.5% of the variance in digital credit and 56.3% in economic sustainability. Mediation analysis further confirms that digital credit partially mediates the relationship between FOMO and economic sustainability. The findings highlight the need for financial literacy initiatives, transparent credit practices, and responsible borrowing to mitigate the adverse effects of FOMO and promote household economic resilience.